Foundation of international macroeconomics - Obstfeld, Maurice; Rogoff, Kenneth (Cambridge, Mass : The MIT Press, 1996)
Economics
2004-06-21
Keywords: International macroeconomics; International economic relations; International financial markets; International capital markets